Immunohistochemical Evaluation of Growth Factors in the Peripheral Blood Vessels of Patients with Severe COPD and Osteoporosis - Igor V. Manzulo (Journal of Global Pharma Technology, 2018)
The expression of vascular endothelial growth factor (VEGF) and transforming growth factor beta (TGFβ) in the blood vessels of striated muscle specimens of 20 severe chronic obstructive pulmonary diseases (COPD) with osteoporosis and healthy subjects were assessed by immunohistochemistry method with using immunoperoxidase reaction with monoclonal and polyclonal specific antibodies. The serum levels of VEGF and TGFβ were studied in 74 severe COPD patients and 36 healthy individuals using immynoenzyme (ELISA) methods. Elevated level in TGF-β and reduced serum VEGF were associated with low bone mineral content and muscle mass in the COPD patients. Increased expressions of TGF-β2 and VEGF were observed in the vascular wall in the severe COPD group with osteoporosis. Intensities of staining in the arterial structures were higher in the COPD group, which were primarily presented in the endothelial and muscular layers. Thus, our study strengthens the hypothesis that change tissue and serum markers of the vascular remodeling are involved in pathophysiology of bone damage in severe COPD.Keywords: Chronic Obstructive Pulmonary Disease, Osteoporosis, Vascular Endothelial Growth Factor, Transforming Growth Factor Beta, Vascular Dysfunction.